Potensi minyak atsiri daun jeruk purut sebagai fumigan nabati terhadap Araecerus fasciculatus (De Geer) (Coleoptera: Anthribidae) pada biji kakao di tempat penyimpanan - Putri Dela Atikah; Idham Sakti Harahap; Dewi Sartiami (Jurnal Entomologi Indonesia, 2022)
Cocoa (Theobroma cacao) is one of the important commodities in Indonesia. The quality of cocoa beans has decreased during storage, one of which is due to the attack of Araecerus fasciculatus (De Geer). This pest attack can be overcome by fumigation that is safe for the environment through the use of essential oil. The study aimed to examine the mortality and repellent effects of kaffir lime leaves essential oil (KLLEO) to A. fasciculatus and to analyze the compound content of active fraction KLLEO using GC-MS. Research stages included maintenance and insect rearing, toxicity and repellency tests, fractionation, and analysis of active fraction compounds of essential oils. The study was designed using CRD with 6 treatments and 4 replications. The n-hexane fraction of KLLEO caused the highest mortality of A. fasciculatus adults after 72 hours of fumigation. The LD50 and LD95 values of the n-hexane fraction of KLLEO were 0.30 and 1.66 ml/l air, respectively. The dose at 1 ml/l air caused the highest mortality of A. fasciculatus adult by 73.75%. Examine using an olfactometer, KLLEO has high repellency against adult A. fasciculatus with the value of the repellency index reaching 100% at 1 ml/l air. The most dominant compound in the n-hexane fraction of KLLEO was the citronellal. Therefore, the KLLEO has some potential to be expanded as a botanical fumigant towards A. fasciculatus.